Sports and the pursuit of gender equality: The role of female students' participation intentions at Universiti Putra Malaysia - Amin, Samir Muhazzab; Mohd Yussof, Nur Ziyan Zahirah; Nazuri, Nur Shuhamin; Ahmad Suhaimi, Siti Shazwani (Human Resources Management Academic Research Society (HRMARS), 2023)
This study explores the role of personal attributes in shaping the intention to participate in sports among female students at Universiti Putra Malaysia. The research aims to determine the level of women's involvement in sports, identify factors that drive or hinder their participation, and examine the relationship between stereotypes and sports involvement. A total of 214 female students from the Faculty of Human Ecology participated in the study, providing data through a self-administered questionnaire. The Personal Attributes Questionnaire was used to measure individual masculinity and femininity, while Intention to participate were assessed using Cassidy and Shaver's scale. The findings indicate that the personal attributes are a significant driving factor for women's sports intention to participate. The study found that level of representation does not play a significant role in influencing an individual's intention to participate in sports, and it does not affect the relationship between personal attributes and sports participation intention. Overall, the research suggests that personal attributes have a stronger influence on women's sports participation intentions than the level of representation alone. It is recommended that future studies explore additional factors that can motivate women to engage in sports and consider a larger sample size to enhance the research methodology.